The state of the agri-, food-, and climate-tech innovation ecosystem in Egypt - Vitón, Roberto; Al-saffar, Reem; Menza, Gianpiero; Zaccari, Claudia; Dowling, Kevin (2024)
The agriculture sector in Egypt is vital to sustaining Egyptian livelihoods and economic development. A thriving agri-, food-, and climate-tech environment, catalyzed by cutting-edge technology and context-oriented innovations is crucial to this development to ensure the resilience of its agrifood systems in the face of climate change, climate extremes, and a dwindling freshwater supply. Agriculture utilizes the greatest share of Egypt’s freshwater resources, primarily sourced from the Nile. This reliance, coupled with Egypt’s high evaporation rates, underscores the urgent need for innovative solutions. Over the last decade, Egypt’s agri-, food-, and climate-tech sector has grown, driven by digitalization and supported by various stakeholders. With close to a hundred startups therein, the sector attracts youth, creates jobs, and supports economic development. However, achieving a sustainable future requires adopting science-based solutions, many of which remain stacked at the concept stage, never to be deployed in the market. Therefore, it is the role and responsibility of players within the agricultural research and technology sector to bridge this gap and speed up the translation of innovative ideas into actionable solutions through market mechanisms that guarantee the viability of these solutions. We must ensure that all key actors are onboard if we are to realize this vision. This report serves as a valuable resource for understanding the critical components of the Egyptian agri-, food-, and climate-tech ecosystem and its enablers and drivers. The conclusions and recommendations arising from this report combine an understanding of policy implications, sustainable business models and vital solution areas relevant to the Egyptian context, providing insights applicable to policymakers, investors, researchers, and other stakeholders operating in the Egyptian agriculture sector. Although this innovation ecosystem has progressed in recent years, it is still largely in its early stages. This report highlights a possible path for addressing key challenges and creating the conditions needed for agri-, food-, and climate-tech innovation to flourish. We at the CGIAR Accelerate for Impact Platform hope that this resource will prove a practical tool for guiding stakeholders in fostering a robust and sustainable innovation ecosystem in Egypt.